Comparison of the structure and musculature of male terminalia in the tribes Operophterini, Phileremini and Triphosini (Lepidoptera: Geometridae: Larentiinae) - Schmidt, Olga (Zootaxa, 2017)
The skeleton and musculature of the male terminalia are described and illustrated for the tribes Operophterini Packard, Phileremini Pierce and Triphosini Tutt (Lepidoptera, Geometridae, Larentiinae), with Solitaneini Leraut included in the discussion. Nine genital muscles, typical of the subfamily, were identified. The previously uncertain separation of Triphosini from Rheumapterini Herbulot is confirmed, based on the morphology of male terminalia, including the position of extensors and flexors of the valvae. Based on the morphology, a close relationship of the Phileremini, Solitaneini, Triphosini and also Operophterini is suggested. Additionally, some notes on the most recent molecular phylogeny of the Larentiinae are included.